AI-driven teaching and the development of future-ready talent among university students in Malaysia: Aligning higher education with sustainable development goals (SDG) - Ahmad , Nurul Zamratul Asyikin; Rahim, Hainnuraqma; Abdul Azis, Rafidah; Ismail, Maymunah; Adam, Muhammad Afiq (Journal of Islamic, Social, Economics and Development, 2026)
The rapid advancement of Artificial Intelligence (AI), digital transformation, and Industry Revolution 5.0 has significantly reshaped higher education, requiring universities to develop graduates equipped with future-oriented competencies. This study investigates the influence of AI-driven teaching on the development of future-ready talent among university students in Malaysia. Grounded in Self-Determination Theory and Constructivist Learning Theory, the study proposes a conceptual framework examining the direct and indirect relationships between AI-driven teaching, student engagement, self-directed learning, and future-ready talent. AI-driven teaching is conceptualised as an innovative pedagogical approach that enhances learning through personalised instruction, intelligent learning systems, adaptive technologies, and automated feedback mechanisms. The study posits that AI-driven teaching positively influences student engagement, which subsequently enhances self-directed learning and contributes to the development of future-ready talent characterised by adaptability, critical thinking, digital literacy, creativity, collaboration, and problem-solving competencies. Furthermore, student engagement and self-directed learning are proposed as key mediating mechanisms explaining how AI-enhanced educational environments foster graduate readiness for future employment landscapes. The study contributes to the theoretical advancement of AI-enhanced learning research by extending the application of Self-Determination Theory within higher education contexts. Practically, the findings are expected to provide valuable insights for educators, higher education institutions, and policymakers in designing sustainable AI-driven pedagogical strategies that strengthen graduate employability and workforce readiness. The study also supports the achievement of Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure), by promoting inclusive digital learning, technological innovation, and sustainable talent development..